Does pregnancy have any impact on long term damage accrual and on the outcome of lupus nephritis?. (November 2017) - Gianfreda, Davide; Quaglini, Silvana; Frontini, Giulia; Raffiotta, Francesca; Messa, Piergiorgio; Moroni, Gabriella
Abstract: No data are available about the impact of pregnancy on the long-term outcome of lupus nephritis. Thirty-two women with lupus nephritis with a 10-year follow-up after their first pregnancy ("women who gave birth") and 64 matched controls with the same follow-up and who never had pregnancies ("controls") were compared for the occurrence of SLE flares, chronic kidney disease (CKD), and SLICC/ACR Damage Index (SDI) in the post pregnancy period. The same evaluations were done before and after pregnancy in women who gave birth. The predictors of CKD and damage accrual in the whole population were studied. All patients were Caucasians and had biopsy proven LN. At conception and after 10 years, in both groups, less than 10% of patients had active renal disease (p = ns). Controls had more frequent arterial hypertension (p = 0.025). Between the two groups there was no difference in SLE flares and in CKD free survival curves (p = 0.6 and p = 0.37) during the 10-year follow-up. In both groups, the temporal trend, based on annual evaluation, of glomerular filtration rate and serum creatinine shows a significant decrease and increase respectively. However, the women who gave birth persistently maintained better values of renal function than controls during the whole follow-up (P = 0.00001). There was no difference in the CKD-free survival curves. SDI did not increase significantly in women who gave birth in comparison to controls. All the above mentioned clinical parameters were comparable before and after pregnancy in the women who gave birth. Among the basal clinical characteristics, high serum creatinine and occurrence of SLE flares predicted CKD, whereas low levels of C3, pre-existing damage score, and occurrence of SLE flares predicted SDI increase. Pregnancy was not a predictor of CKD or SDI increase. Carrying a pregnancy during inactive lupus nephritis does not seem to increase the rate of SLE flares, worsen renal prognosis or increase SDI significantly in the very long-term. Highlights: This study is the first on lupus nephritis outcome 10 years after a pregnancy. SLE flares rate was similar before and after pregnancy in women who gave birth and compared to controls. At 10 years, chronic kidney disease (CKD) free survival curves were similar between women who gave birth and controls. In women who gave birth, increase in damage accrual was similar before and after pregnancy and compared to controls. In lupus nephritis, pregnancy was not a predictor of CKD or damage accrual.